Association of Blood Groups with Coronavirus Disease (COVID-19) - Shireen Jawed; Benash Altaf; Hania Ali; Hira Zahid; Anam Rehman (Journal of University Medical & Dental College, 2022)
ABSTRACTBACKGROUND & OBJECTIVE: Coronavirus (covid-19) disease emerged acutely and suddenly, becoming a nightmare as it affected every country drastically. This disease engulfed the physical, mental as well as social lives of the individuals. The objective was to determine which blood group has a higher tendency to contract COVID-19 infection and to evaluate common presenting symptoms.METHODOLOGY: This cross-sectional study was performed from August to September 2020 at Aziz Fatima Medical and Dental College, Faisalabad. A structured questionnaire was formed on a Google form. It was then conveyed through sharing link by WhatsApp among the COVID positive patients. Data was compiled and analyzed by SPSS 22.RESULTS: Our study comprised 415 subjects of age 20-50 years who got COVID-19 infection. Out of which 162(39%) comprise the male population and 253(61%) constituting of female population. Subjects of the age group of 20 to 30 years were most frequently infected with COVID-19. Our results reveal that COVID-19 was more among blood group B followed by O, AB & A. The most frequent symptom from which the subjects suffered was fever 305(73.4%) followed by smell and taste alteration comprising 180(43.3%), 154(37%) subjects suffered from sore throat. GIT symptoms were reported by 50(12.0%) while only 102(13%) remained asymptomatic.CONCLUSION: We conclude that COVID-19 was more prevalent among blood group B followed by O, AB, A, and the Rh-positive group. The most frequent symptom in our study was fever, followed by loss of taste and smell sensation.